Vampire Park - Hall, Willis (Random House UK Ltd, 1997)
Back home after a trip abroad, Count Alucard, the vegetarian vampire, is surprised to find a stranger living in his castle. This turns out to be none other than Freddie, the Count's long-lost cousin.
Keywords: Juvenile literature-Vampires-Fiction